Persepsi Mahasiswa Ilmu Perpustakaan terhadap Penggunaan Perangkat AI LLM dalam Pencarian Informasi - Zahra, Danisya Laila; Wibowo, Muhamad Prabu (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
The increasing use of generative artificial intelligence (AI) among university students is driving changes in the way they seek and manage information, including in academic contexts. ChatGPT and DeepSeek AI are two AI platforms based on Large Language Models (LLMs) that are increasingly utilized as tools to support information seeking processes. This study aims to analyze the preferences of students from the Library and Information Science Program, Faculty of Humanities, Universitas Indonesia (FIB UI), in using these two platforms. The research employs a case study method with a qualitative approach, involving in-depth interviews with ten students. This study explores their motivations, usage frequency, academic and non-academic benefits, differences in user experience, alignment with the field of library science, and technical challenges in using ChatGPT and DeepSeek. The findings show that students prefer ChatGPT due to its ease of use, speed, and user-friendly interface. Meanwhile, DeepSeek AI is considered superior in terms of technical accuracy, especially for academic tasks requiring precision, such as metadata processing and classification. User preferences are influenced by perceived usefulness, ease of use, performance expectations, social influence, and technical support. The study concludes that the alignment between academic needs and the technological features offered by LLM-based platforms is a key factor in students’ selection of AI-assisted tools.